Wyposażenie rodzinnych gospodarstw domowych w dobra trwałego użytku - Bednarek, Bronisław (Wydział Prawa i Administracji UAM, 1989)
The article presents the results of research conducted by the Statistics and Demography Department of the Academy of Economics in Poznań on the variability of level of durable goods in family households. The research was based on household budget data gathered by the Chief Statistical Office. The resarch showed that in the 1980s in Poland there appears the diversification among households as to the number of durable goods. Relatively best equipped are employee households, worse — peasant and peasant-worker households, and the worst — retired persons households. Also spatial diversification in that respect can be observed. The author also attempts to identify the selected factors conditioning the number of durable goods in family households. It was carried out by means of one of linear regression methods (a posteriori elimination procedure). It made it possible to discover numerous demographic and economic regularities in that respect.
Durable goods in family household